2017
DOI: 10.1175/jcli-d-16-0451.1
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Global Climate Models Struggle to Represent Low-Level Clouds in the West African Summer Monsoon?

Abstract: Climate models struggle to realistically represent the West African monsoon (WAM), which hinders reliable future projections and the development of adequate adaption measures. Low-level clouds over southern West Africa (5°–10°N, 8°W–8°E) during July–September are an integral part of the WAM through their effect on the surface energy balance and precipitation, but their representation in climate models has received little attention. Here 30 (20) years of output from 18 (8) models participating in phase 5 of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
91
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(96 citation statements)
references
References 62 publications
5
91
0
Order By: Relevance
“…Hannak et al [40] showed that in the region of West Africa there are large and persistent low cloud fields. They postulated that the self-calibrating method of the Heliosat algorithm leads to an underestimated effective cloud albedo in the region with persistent cloud cover, since the scenes with minimum number of counts are still contaminated with clouds [40]. This leads to a strong overestimation of surface radiation and SDU in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Hannak et al [40] showed that in the region of West Africa there are large and persistent low cloud fields. They postulated that the self-calibrating method of the Heliosat algorithm leads to an underestimated effective cloud albedo in the region with persistent cloud cover, since the scenes with minimum number of counts are still contaminated with clouds [40]. This leads to a strong overestimation of surface radiation and SDU in this area.…”
Section: Discussionmentioning
confidence: 99%
“…3). These diagrams also indicate different phases of the monsoon season, which were distinguished by Knippertz et al (2017) mainly based on the north-south precipitation difference between the coastal and the Soudanian-Sahelian zones. These are: the pre-onset phase characterized by a rainfall maximum near the coast (before 21 June, phase 1); the post-onset phase during which the rainfall maximum occurred inland 30 (22 June -20 July, phase 2); the wet westerly regime when the rainfall maximum shifted back to the coast (21 -26 July, phase 3); and the recovery of the monsoon with a shift of the rainfall maximum inland (27 July until the end of the campaign, phase 4).…”
Section: Measurement Sites and Available Observationsmentioning
confidence: 97%
“…According to van der Linden et al (2015), their extent covers an area of about 800 000 km 2 . As the clouds often persist long into the following day, they control the daytime 5 radiative energy supply at the Earth's surface and, hence, influence the diurnal cycle of the atmospheric boundary layer (ABL) and, by this, they considerably affect the regional climate (Knippertz et al, 2011;Hannak et al, 2017). Up to now, high-quality data in this region are rare and only a few model investigations have been performed to investigate the temporal evolution and spatial distribution of LLCs in this region (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cloud cover over West Africa is an important feature of the African monsoon but is poorly represented by global models (Hannak et al, 2017). This could lead to too low simulated clouds and too high incoming radiation at the surface that imply too high diurnal cycles of temperature and relative humidity over this region.…”
mentioning
confidence: 99%